Economic efficiency analysis of fish farming in Bharatpur District, Rajasthan: A corporate social responsibility (CSR) initiative - Bunkar, Khemraj; Prakash, Swadesh; V. Ramasubramanian; Krishnan, M.; Kumar, N R (Indian Journal of Fisheries, 2022)
The innovative corporate social responsibility (CSR) initiative of Lupin Human Welfare and Research Foundation, Bharatpur, Rajasthan, India, through fish farming in Kaman Block of Bharatpur has transformed the lives of the local population. Fish farming started with 240 families in 1980, is now benefiting 2000 people and has brought economic and social transformation in this region. Cost-benefit analysis indicated that fish farmers culturing Indian major carps (IMC) for 18 months from spawn to table size registered a benefit-cost ratio (BCR) of 2.15. The fish farmers who cultured IMC for 12 months (from fingerlings to table size ) achieved a BCR of 1.77. The results of data envelopment analysis (DEA) showed that the technical efficiency was around 0.95, indicating highly efficient farms. Polluted water, disruption in power supply and poaching were found to be major constraints faced by the farmers. Keywords: Constraint analysis, Costs and returns analysis, Data envelopment analysis, Indian major carps